Examination of Advertising on Social Media: The Role of Endorsers in Creating Brand Awareness - Tulastri; Arie Indra Gunawan; Rafiati Kania (Journal of Marketing Innovation (JMI), 2022)
This research aims to measure the effectiveness of advertising in the consumer goods market, as well as to determine the effectiveness of advertising conducted on social media in creating brand awareness. By employing exploratory research with a quantitative approach, 389 data were obtained. The results of this study show that the measurement of advertising effectiveness can be done through celebrity endorsers, message content, and the use of social media. In addition, the effectiveness of advertising has a positive and significant influence on the creation of brand awareness. In details, celebrity endorsers or well-known public figures do not guarantee the formation of brand awareness. This research recommends a collaboration between celebrity endorsers who portray a good image with feasible budget supported with the appropriate messages and media with the right target audience, so the consumer goods advertising can be effective.